СТОРИТЕЛЛИНГ МАКТАБДА ФИЗИКАНИ ЎҚИТИШНИНГ ИННОВАЦИОН МЕТОДИ СИФАТИДА - Ерлепесова, И. (SCIENCE and SOCIETY, 2025)
The article examines the use of the story-telling method as an effective method of teaching physics at school. The theoretical foundations of the method are analyzed and are given practical examples of its implementation and recommendations for pedagogues are given.